(untitled) (Veterinary Science Development, 2015)
Opportunistic and intestinal parasite infections are common health problem among HIV/AIDS patients. Early detection and treatment of these parasites are important to improve the quality of life of this category of patients. The occurrence of intestinal parasites among 400 patients on highly active anti-retroviral drug therapy (HAART) aged 11-60 years was investigated. Standard parasitological techniques like direct microscopy, formol ether concentration and modified Ziehl- Neelsen staining techniques were used to analyze the stool samples. Intestinal parasite infections were positive in 116 (29%) of the subjects on HAART while control subjects had 12 (12%) and the difference was statistically significant (P<0.05). Subjects in the age group 21-30 years had the highest infection rate 54 (35.1%). There was no statistically significant difference in infection according to age (P>0.05). Females 76 (32.5%) had a higher prevalence rate than males 40 (24.1%). But there was no statistically significant difference in infection according to gender (P<0.05). Patients with CD4 count of less than 200 cells/mm3 were observed to be more infected than those with CD4 count of more than 200 cells/mm3. There was a strong positive correlation (r=0.94) between CD4 count and the occurrence of intestinal parasite infection. Protozoan parasites 84 (21.0%) accounted for a higher prevalence rate than helminthic parasites 32 (8.0%). These findings has revealed a high prevalence of intestinal parasite infection among patients on HAART thus the routine screening of stool samples from these category of patients for intestinal parasites is advocated for effective management of the disease.